POTENSI PASAR RABU GALING DALAM MENINGKATKAN PEREKONOMIAN PEDAGANG MUSLIM DI DAERAH PERBATASAN ARUK – MALAYSIA - Wahab Wahab; Iva Ashari Ananda; Juni Sherven (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
This research is motivated by indications that the market is one of the efforts to improve the economy, such as selling daily necessities. This effort is expected to enable traders to create better economic conditions than before. Especially in meeting the needs of traders in the market. So that this achievement can be carried out optimally, it is considered necessary to explore the existing potential to be developed further. Based on the results of the study concluded that Pasar Rabu has the potential to increase the economy of Muslim traders in Galing District, Sambas Regency, because it provides satisfaction and the specified target is always achieved. There are supporting factors in the economic improvement in the Wednesday Market, including adequate human resources, well-managed natural resources, the ability to use technology and capital resources smoothly and access to adequate health and security levels are maintained. While the inhibiting factors are the lack of government attention, the unavailability of the infrastructure needed by traders and also the occurrence of inflation.